The Suyunakuy - Vivanco Flores, Carlos A. (1971)
The "suyunakuy" consists of the enthusiasm and activity that come from the lamperos or day laborers in the cultivation of corn and. The individual who finishes the designated task before others is called captain and the last of all qollana.